The Effect of Mental Health Education On Pre University High School Girls Concerning Their Attitude Beliefs, and The Knowledge Towards The Subject - M Erfani Khanghahi (مدیریت سلامت, 2004)
Introduction: Considering the significance of mental health as an inseparable part of human health, and in view of its high prevalence and severe long disabling effect, and the role that people's knowledge and belief have in utilizing mental health services, this research was performed with the purpose of studying the effects of mental health education on the awareness, belief and attitude of high school girl students at pre-university phase, in the year 2001-2002 in Tehran. Methods:In this quasi-experimental study, Tehran's 7Th educational district was selected for the study. With the application of randomized cluster sampling method, 150 high school girl students from two pre-University phases were chosen. Samples were evaluated at two stages, before the implementation of the educational program and after, by using a questionnaire including the awareness level of mental problems (anxiety, depression), their attitude towards mental problems, self-concept and existing variables. The results were analyzed, using paired T test, one way variance analysis and Schaffer test. Findings: Results of paired T-test between the mean score of knowledge, components of health belief model and self concept scores of students indicated significant difference before and after educational program implemented (P<0.0005). Results: Mental health education has a positive effect on knowledge, beliefs, attitude and self-concept of people. This study is considered to be a beginning to more future research in this field